1, 3, 4‐Oxadiazole‐2(3H)‐thione Analogs as PIM Kinase Inhibitors. (28th September 2020) - Hong, Victor Sukbong; Jeong, Seungik; Yun, Yanghwan; Choo, Hyeonseong; Won, Jongin; Lee, Jinho
Abstract : Proviral integration site for moloney murine leukemia virus (PIM) kinases are highly expressed in hematological cancers. They phosphorylate downstream substrates that contribute to tumor growth and survival. Therefore, a potent inhibitor of PIM kinases is expected to be effective at treating hematological cancers. In the present study, several indole derivatives of 1, 3, 4‐oxadiazole‐2(3 H )‐thione were synthesized and evaluated as PIM kinase inhibitors. Structure–activity relationship studies yielded potent inhibitors of all three PIM kinases in the single‐digit to low double‐digit nanomolar IC50 range. Kinase profiling of a representative compound showed high selectivity among 15 other kinases. Abstract : Chemical structure and biological activities of 9d.